Analisis Dampak Perubahan Iklim terhadap Produktivitas Perkebunan Karet terhadap Kesejahteraan Petani di Kabupaten Musi Rawas - Syabawaihi, Syabawaihi; Ira Primala Sari; Vera Octalia (Yayasan Literasi Sains Indonesia, 2025)
Climate change has become a global issue with significant impacts on various sectors, including agriculture and plantations. This study aims to analyze the impact of climate change on the productivity of rubber plantations and the welfare of farmers in Musi Rawas Regency, South Sumatra. Musi Rawas is a region with significant rubber production potential, yet the increasingly extreme climate change poses a threat to the sustainability of rubber plantations, which in turn affects farmers' welfare. This study uses a quantitative approach with regression analysis to measure the relationship between climate change variables, rubber productivity, and farmers' welfare. Data were collected through surveys conducted with rubber farmers in several districts in Musi Rawas, considering factors such as rainfall, temperature, and wind patterns. The results indicate that rising temperatures and fluctuating rainfall patterns have a negative effect on rubber productivity, causing a decline in yields and increasing operational costs for plantation maintenance. This leads to reduced income for farmers, which ultimately affects their welfare. Additionally, farmers who rely on predictable planting seasons are under pressure due to the uncertainty caused by climate change. Therefore, better adaptation measures are needed, such as the use of rubber varieties more resistant to climate change and the application of environmentally-friendly agricultural technologies to increase resilience to climate change. This study provides useful insights for policymakers in formulating programs to strengthen farmers' resilience to the impacts of climate change.